First study of metal hybrids of boronic acids: second-sphere coordination networks in the structures of 4-carboxyphenylboronic acid with some transition metals - Seethalekshmi, N.; Pedireddi, V. R. (Inorganic Chemistry, 2006)
Metal-organic hybrids of a boronic acid (4-carboxylphenylboronic acid) with Co(II), Mn(II), and Ni(II) salts have been reported for the first time. In all of the complexes, there is no interaction between the metal and boronic acid through dative bonds. Furthermore, second-sphere coordination, along with water clusters in the form of octamers, was observed in the absence of any other additional ligands. However, in the presence of aza-donor molecules such as 1, 2-bis(4-pyridyl) ethane, metal ions formed coordination polymers with those ligands, replacing the second-sphere coordination.